Becoming an Afro-diasporic subject: working with Du Bois, Frantz Fanon and Stuart Hall - Flor, Caue Gomes [UNESP]; Kawakami, Erica A.; Silverio, Valter R. (Univ Sao Carlos, Dept Sociology Federal, 2021)
What is it to be Black? What are the contours of this subjectivity and the conditions that position this subject in the networks, flows, forces and narratives that institute it? The task that we propose in this article, is to offer a genealogical path way about the how in which such questions, coextensive with different black intellectual traditions and modernity itself, took shape and crossed the formulations of three specific intellectuals: W. E. B. Du Bois, Frantz Fanon and Stuart Hall. We have argue that not only is there both a route between the thinking of these scholars, which offers a critical status for speculation about the constitution of such a subject/subjectivity, as there is between them and the black intellectual traditions that represent the following proposition: there is possible to enunciate a existence that is not neither oppositional nor reactive, but becoming yourself an Afro-diasporic subject.
Keywords: afro-diasporic subject; african diaspora; difference; black intellectuals